MODEL PEMBANGUNAN BERKELANJUTAN BERBASIS EKONOMI MARITIM DI INDONESIA - Budi Rusdianto; Nuri Rahayu Ningsih; Suhendi Suhendi; Andria Zulfa; Rusiadi Rusiadi; Diwayana Putri Nasution (Jurnal Bina Bangsa Ekonomika, 2024)
This research was conducted in Indonesia with the aim of determining the sustainable development model based on maritime economy using the Vector Autoregression (VAR) analysis method with time series research data for 15 (fifteen) years. The variables used in this study consisted of exports, imports, loading sea freight (ALM), and bongkatr sea freight (ALB) with data obtained through the Central Bureau of Statistics (BPS) Indonesia. The results of the VAR analysis show that the contribution of each variable to itself and other variables is clearly visible on the basis of lag 1. Vector autoregression analysis reveals significant interrelationships between variables, reflecting the complexity and interconnectedness within those systems. The Impulse Response Function (IRF) showed an increase in exports giving a positive response in all time periods, however, a negative response appeared in the medium and long term from the import variables, ALM and ALB. Import variables give positive responses in various time periods, but negative responses appear in the medium and long term from imported variables, ALB, and ALM. Response stability is established in the medium term (period 5) and long term (period 10). Forecast Error Variance Decomposition (FEVD) analysis shows that export variables contribute significantly to model changes in the short term, while export and import variables are more effective as recommendations for development model development in the medium and long term. Development models through variable ALM most effectively involve ALB in the short term, and ALB and exports in the medium and long term. Import control is effective in controlling export variables in the short, medium, and long term. Overall, the results of FEVD analysis provide deep insights for the development of maritime economy-based development models in Indonesia, emphasizing the importance of export, import, ALB, and ALM variables in formulating effective policies.